High efficient thermochemical energy storage of methane reforming with carbon dioxide in cavity reactor with novel catalyst bed under concentrated sun simulator. (April 2022) - Lu, J.F.; Dong, Y.X.; Wang, Y.R.; Wang, W.L.; Ding, J.
Abstract: Thermochemical energy storage performance of methane reforming with carbon dioxide in cavity reactor under concentrated sun simulator has been experimentally and numerically studied. Novel catalyst bed with Ni/Al2 O3 particles and perforated quartz encapsulation is proposed to perform high bed temperature for greenhouse effect, and then chemical energy storage efficiency and total energy utilization efficiency of experimental system can respectively reach as high as 41.1% and 80.3%. As concentrated heat flux increases or reactant flow rate decreases, methane conversion rises with bed temperature increasing, while chemical energy storage efficiency first rises and then falls for larger heat loss. As inlet mole fraction of methane increases, chemical energy storage efficiency firstly increases and then drops. Numerical model of cavity reactor under concentrated heat flux is established and validated. In catalyst bed, maximum reaction rate occurs near focal point, while reverse reaction occurs near its side. With the improvement of porosity in catalyst bed, methane conversion and thermochemical storage efficiency firstly increase and then decrease, while they gradually increase with heat conductivity of bed rising. In addition, optimal concentrated heat flux, flow rate, mole fraction of methane (0.5) and bed porosity (0.6) are derived for maximum chemical energy storage efficiency.